Structural and magnetic properties of CuCo films electrodeposited in the presence of trisodium citrate - Paula, F. R. de [UNESP]; Oestereich, A. L.; Zago, L. A.; Spada, E. R. (Springer, 2016)
The structure and magnetic properties of CuCo alloys electrodeposited in aqueous solution on n-type Si(100) substrates were investigated as a function of the trisodium citrate concentration in the electrolyte. The compositional analysis show that percentage of Co has a non-monotonic dependence on the increase in concentration of sodium citrate, with a maximum at 300 mM followed by a significant decrease The magnetic measurements in similar samples in terms of composition and thickness show that the coercive field value it differs greatly, from 87 to 20 Oe without and with added citrate, respectivelly, owing to the improved morphological quality and change in crystalline structure induced by the citrate. For electrodeposited films without citrate in the electrolyte, the X-ray diffraction pattern shows two peaks at 2 theta = 43.298 and 44.217 typical of fcc (111) planes for copper and cobalt, respectively, while in the presence of citrate only one peak characteristic of fcc of the CuCo alloy was observed.